International new ventures: Revisiting the influences behind the ‘Born-Global’ firm - FAN, Terence P. C. (Institutional Knowledge at Singapore Management University, 2018)
There is a small but theoretically important literature on 'born-globals' or international new venture firms that positions itself in contrast to the more established sequential international entry literature. In this paper we examine the pattern of entry into international markets for a set of international new ventures and show that they need not be a distinct breed of firms, as previous research has portrayed. Absent a specific technological advantage, the decision for a new venture to internationalize at inception is influenced by the size of its home market and by its production capacity, as well as by cultural and economic forces that also influence other more traditional firms that stage their entry into international markets. Most importantly, we demonstrate that the decision to internationalize or not should be considered jointly with the capacity allocation decision to specific international markets, as analyzing these separately may lead to biased results.